Teacher Strategies in Civic Education for Internalizing Tolerance Values as Social Conflict Prevention in Multicultural Schools - Rihla Azmira; Syarbaini Saleh (Papanda Publisher, 2026)
This study examines strategies employed by Civic Education (PPKn) teachers in internalizing tolerance values as conflict prevention efforts at SMA Negeri 1 Medang Deras, a multicultural secondary school in North Sumatra, Indonesia. Grounded in Berger and Luckmann's social construction theory, the research addresses the knowledge gap regarding how PPKn teachers operationalize tolerance education in heterogeneous school environments. A descriptive qualitative design was employed, collecting data through classroom observations, semi-structured interviews with teachers and students, and document analysis during April-July 2025. Purposive sampling identified PPKn teachers as key informants, eleventh-grade students as primary informants, and school administrators as supporting informants. Data analysis followed Miles et al.'s interactive model, employing triangulation to ensure trustworthiness. Findings reveal five synergistic strategies: value-based learning integrating tolerance into curriculum content, problem-based learning addressing real social issues, teacher role modeling demonstrating respectful behavior, contextual teaching linking theoretical concepts to students' lived experiences, and reflective practices encouraging critical self-examination. These strategies successfully transformed abstract tolerance concepts into concrete behavioral dispositions, evidenced by students' spontaneous promotion of tolerance beyond instructional contexts and increased comfort among minority students. The study validates social construction theory in educational settings, demonstrating how tolerance values undergo externalization through teacher modeling, objectification within classroom culture, and internalization through student meaning-making. Results offer evidence-based guidance for educators implementing tolerance education in multicultural contexts while identifying the necessity of multi-strategy approaches for effective values internalization.